Visit-to-visit variability of metabolic parameters and risk of heart failure: A nationwide population-based study. (15th October 2019) - Kwon, Soonil; Lee, So-Ryoung; Choi, Eue-Keun; Lee, Seung-Hwan; Han, Kyung-Do; Lee, Seo-Young; Yang, Seokhun; Park, Jiesuck; Choi, You-Jung; Lee, Hyun-Jung; Moon, Inki; Lee, Euijae; et al.
Abstract: Background: This study examined the effects of variability of four metabolic parameters, namely systolic blood pressure (BP), body mass index (BMI), fasting blood glucose (FBG), and total cholesterol level (TC) on the risk of HF. The effects of metabolic parameter variability on the risk of heart failure (HF) remain unclear. Methods: We studied individuals aged ≥40 years who had undergone ≥3 health check-ups under the Korean National Health Insurance Corporation during 2009 and 2012, and those who did not have hypertension, diabetes, or dyslipidemia. BP, BMI, FBG, and TC were measured at every visit. We defined the variability of each parameter using the variability independent of the mean (VIM) method. VIMs were categorized into four groups according to quartiles. The metabolic variability (MV) score for each subject was defined as the number of VIMs in the highest quartile. Results: Among the 3, 820, 191 subjects, 17, 253 (0.45%) had incident HF during a mean 5.3 ± 1.1 years of follow-up. High variability of each parameter was associated with increased HF risk, which increased according to the MV score. After multivariable adjustment, compared to subjects with MV score = 0, subjects with MV score = 1–4 had an increased risk of HF (adjusted HR [95% CI], 1.15 [1.10–1.19] for MV score = 1, 1.33 [1.28–1.39] for MV score = 2, 1.48 [1.40–1.57] for MV score = 3, 1.74 [1.55–1.96] for MV score = 4 [p-for-trend ≪0.0001]). Conclusions: High variability of BP, BMI, FBG, and TC was synergistically associated with a higher incidence of new-onset HF. Highlights: Multiple metabolic parameters with high variability are associated with incident heart failure in synergistic fashion. High variability in metabolic parameters is also associated with incident heart failure even in healthy adults. High variability in metabolic parameters may be regarded as a surrogate marker of heart failure development.